Factors Affecting The Income of Edamame Farmers (A Case Study in Sindangsari Village, Lembursitu Subdistrict, Sukabumi City) - Noviyanti Dewi; Amalia Nur Milla; Neneng Kartika Rini (Advances In Social Humanities Research, 2026)
This research aims to determine the effects of production volume, edamame price, education level, farmer age, number of workers, land ownership, and land area on the income of edamame farmers, as well as identify the variables with the strongest influence on farmer income. This study employed a descriptive quantitative research approach. The results showed that, simultaneously, all independent variables (production volume, price, education level, age, number of workers, land ownership, and land area) significantly influenced farmer income, with an F-statistic value of 6.024 > F-table value of 2.64 and a significance value of 0.000 < 0.05. Partially, production volume (t-count = 3.297 > t-table = 2.034, sig. = 0.002) and land area (t-count = 2.610 > t-table = 2.034, sig. = 0.014) had positive and significant effects on income, while price, education level, age, number of workers, and land ownership did not show significant effects. Land area was identified as the variable with the most dominant influence on farmer income. The coefficient of determination (R²) of 0.5210 indicated that 52.10% of income variation was explained by the independent variables, while the remaining 47.90% was influenced by other factors outside the model. These findings confirmed that increasing production volume and expanding cultivated land area were key strategies for improving edamame farmer income in the study area.